Impact of Aluminum Phosphide on the Transferases in Liver and muscle of Parophiocephalus obscurus - Reuben Inyang Iniobong; Chibueze Izah Sylvester; Desmond Okpogholor Kesiena (Journal of Plant and Animal Ecology, 2019)
This study assessed the effect of aluminum phosphide on transferases in liver and muscle of Parophiocephalus obscurus (with mean weight of 42.20±1.5 gSD and mean length of 16.50± cmSD, respectively). The fish were obtained from a private fish farm in Yenagoa Metropolis, Nigeria, and the fish was allowed acclimatized to laboratory condition for 7 days, and then exposed to sublethal concentrations (0.00mg/L, 4.20mg/L, 6.30mg/L and 8.40mg/L) of aluminum phosphide for 14 days. Renewal bioassay was adopted in this study. At the end of the experimental period, the fish was dissected and the muscle and liver were collected, processed and analyzed for alanine aminotransferase and aspartate aminotransferase using colorimetric method. Results of the phosphatase at 0.00mg/L, 4.20mg/L, 6.30mg/L and 8.40mg/L were 94.50±6.44µ/L, 134.47±15.27 µ/L, 106.47±9.21 µ/L and 31.00±3.46 µ/L, respectively (liver), 107.50±9.24, 92.00±6.93 µ/L, 116.50±8.95 µ/L and 146.33±9.33 µ/L respectively (muscle) for aspartate aminotransferase; and 40.00±1.15µ/L, 26.50±3.18µ/L, 14.50±2.02µ/L and 9.80±1.44 µ/L, respectively (liver) and 17.00±1.75µ/L, 8.50±0.87µ/L, 21.00±2.89µ/L and 5.50±0.87 µ/L, respectively (muscle) for alanine aminotransferase. Statistically, there were significant variations (p<0.05) among the various concentration in the transferances. In addition, at some concentration, there was significant variations (p<0.05) between the level of the transferases in the muscle and liver. The significant alteration observed in the various concentrations is an indication that aluminum phosphide is lethal to fish. Therefore, caution should be exercise during the use of aluminum phosphide near biological system.
Keywords: Alanine aminotransferase